Pendampingan Pengelolaan Limbah Organik untuk Meningkatkan Produktivitas Pertanian Ramah Lingkungan di Jayan Canden Jetis Bantul Yogyakarta - Rubini, Rubini; Meirani, Nurmahya; Nabilatul Adila, Luthfi Amalia (STAI Terpadu Yogyakarta, 2024)
This study aims to evaluate the effectiveness of mentoring in organic waste management to improve environmentally friendly agricultural productivity in Jayan Village, Canden Jetis, Bantul, Yogyakarta. The mentoring involved training and workshops that taught composting techniques and other organic waste management practices. The results of the study indicate that after the mentoring, there was a significant change in the method of organic waste management, which had previously been poorly managed. The composting techniques introduced were able to improve soil quality and agricultural yields, while also reducing dependence on chemical fertilizers. Additionally, this program successfully increased the community's awareness of the importance of environmentally friendly farming practices. The study concludes that mentoring in organic waste management can enhance agricultural productivity and support environmental sustainability.